Line Balancing Techniques for Efficiency Improvement in Construction Steel Company - Pulansari, Farida; Sulaiman, Yoga Aulia; Restu (Future Science)
XYZ company is a company engaged in steel construction. This company produces steel construction with several classifications, namely Building Construction (structure) and Mining Construction (Conveyor and Tank). This problem is found in the production process area where the efficiency of the company is not optimal because of the bottleneck between workstations. To increase efficiency and reduce bottlenecks, companies use the Largest Candidate Rule (LCR); Killbridge and the Western Method (KWM); and the Ranked Positional Weights (RPW) Method. After comparing the three methods, LCR has the best results. Production line efficiency is 92.2%, balance delay is 7.8%, and the smoothness index is 14.6 with 11 operators.